Combination of 18F-FDG PET/CT and convex probe endobronchial ultrasound elastography for intrathoracic malignant and benign lymph nodes prediction - Zhi, Xinxin; Sun, Xiaoyan; Chen, Junxiang; Wang, Lei; Ye, Lin; Li, Ying; Xie, Wenhui; Sun, Jiayuan (Frontiers in Oncology, 2022)
Background: Positron emission tomography–computed tomography (PET/CT) and convex probe endobronchial ultrasound (CP-EBUS) elastography are important diagnostic methods in predicting intrathoracic lymph node (LNs) metastasis, but a joint analysis of the two examinations is still lacked. This study aimed to compare the diagnostic efficiency of the two methods and explore whether the combination can improve the diagnostic efficiency in differentiating intrathoracic benign from malignant LNs. Materials and Methods: LNs examined by EBUS-guided transbronchial needle aspiration (EBUS-TBNA) and PET/CT from March 2018 to June 2019 in Shanghai Chest Hospital were retrospectively analyzed as the model group. Four PET/CT parameters, including maximal standard uptake value (SUVmax), SUVmean, metabolic tumor volume (MTV) and tumor lesion glycolysis (TLG), four quantitative elastography indicators (stiff area ratio, mean hue value, RGB and mean gray value) and elastography grading score of targeted LNs were analyzed. A prediction model was constructed subsequently and dataset from July to November 2019 was used to validate the diagnostic capability of the model. Results: A total of 154 LNs from 135 patients and 53 LNs from 47 patients were enrolled in the model and validation groups, respectively. Mean hue value and grading score were independent malignancy predictors of elastography, as well as SUVmax and TLG of PET/CT. In model and validation groups, combination of PET/CT and elastography demonstrated sensitivity, specificity, positive and negative predictive values, and accuracy for malignant LNs diagnosis of 85.87%, 88.71%, 91.86%, 80.88%, 87.01% and 94.44%, 76.47%, 89.47%, 86.67%, 88.68%, respectively. Besides, elastography had better diagnostic accuracies than PET/CT in both model and validation groups (85.71% vs 79.22%, 86.79% vs 75.47%). Conclusion: EBUS elastography demonstrated better efficiency than PET/CT and the combination of the two methods had the best diagnostic efficacy in differentiating intrathoracic benign from malignant LNs, which may be helpful for clinical application.